La « jeunesse algérienne » en lutte. Du rôle politique conflictuel d'une catégorie sociale hétérogène - Thomas Serres (Revue des Mondes Musulmans et de la Méditerranée)
This article looks the various political roles attributed to the notion of "youth" in Algeria. It shows how a conflictual situation implies both positive and negative definitions of a heterogenous social category. Indeed, besides being a category of age, the "youth" is also defined as a generation due to sharing in a common experience. In other words, the ongoing crisis in Algeria implies a persistent insecurity, economic and social blockings but also a lack of leisure activities. At the same time, one can see the similarities between the notion of the "youth" and that of the "people, especially regarding the persistent tendency of the ruling elite to infantilized the entire population, expressing a paternalism that is often understood as contempt. Finally, this article explains how the idea of an "Algerian youth" is tied to the notion that this group has suffered a loss (préjudice) due to the actions of the preceding generations. Thus, on can also define this group politically as it represents the rejection of both the ongoing crisis as well as the gerontocracy that is held responsible for these events.